A new method to solve and refine algebraic inequalities - DRĂGAN, Marius (2025)
In this book the author, teacher Marius Dragan, presents the solving and refinementof some inequalities with higher grade of difficulty. The paperwork isstructured in five chapters.The book is one of high standard, with a high level of difficulty and it is mostlyaddressed to inegalitarians. The majority of the problems also belong to somerenowned authors in the field of expertise such as Vasile Cartoaje, Titu Zvonaru,Marian Tetiva, Florin St˘anescu, Marius Dr˘agan, Arkady Alt, Murray Klamkin,WalterJanous, Michael Bataille, Michael Rosenberg etc. The editing was very clear andthe solutions are concise but complete.